Secondary formation of submicron and supermicron organic and inorganic aerosols in a highly polluted urban area - Yan Zheng; Miao, Ruqian; Qi Zhang; Li, Yaowei; Xi Cheng; Liao, Keren; Koenig, Theodore K.; Ge, Yanli; Tang, Lizi; Dongjie Shang; Min Hu; Shiyi Chen; et al. (Journal of Geophysical Research: Atmospheres, 2023)
Abstract Different adverse health effects of submicron (PM1) and fine particles (PM2.5) may be attributed to their chemical differences, requiring a better understanding of size-resolved composition. Herein, extensive online measurements were conducted across seasons in Beijing by two aerosol mass spectrometers, one of which alternately sampled PM1 and PM2.5. Source apportionment of organic aerosol (OA) indicated that traffic- and cooking-related OA together accounted for ∼20%−30% of the OA mass in PM2.5, showing insignificant seasonal variations. Coal-combustion and biomass-burning-related OA had minor contributions. The two secondary OA (SOA) factors together accounted for 59%−73% of the OA mass in PM2.5. The mass distributions of particulate components in PM1 and PM2.5 varied greatly across seasons. Secondary formation played a key role in particle size growth during cold seasons. During severe hazes with high aerosol liquid water content (ALWC), the supermicron mass fraction (MF1−2.5) of secondary components reached ∼40%−50% while those for primary OA remained at ∼20%. Heterogeneous uptake, aqueous processing, and dissolution likely all contributed to the enhanced concentration of secondary components, and the former two were perhaps more important. The increase of MF1−2.5 for secondary components with increasing ALWC in spring was less than that in winter, possibly due to the shorter duration of stagnant conditions limiting secondary formation. Early autumn showed higher MF1−2.5 values than cold seasons with insignificant changes as ALWC varied, plausibly explained by intensive new particle formation hindering persistent particle growth. Our results highlight the importance of heterogeneous uptake and aqueous processing in distributing SOA in supermicron mode in polluted areas.